2001
DOI: 10.1149/1.1418377
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Corrosion Products Formed on Copper in Urban, Rural/Coastal, and Hot Spring Areas

Abstract: Corrosion products formed on copper plates exposed in urban, rural/coastal, and hot spring areas in Japan were characterized by X-ray photoelectron spectroscopy, X-ray diffraction ͑XRD͒, and coulometric reduction. The exposure tests were carried out for a month in summer. XRD patterns showed that hydrated copper sulfate ͓Cu 4 SO 4 (OH) 6 •H 2 O, posnjakite͔ and cuprite Cu 2 O were formed on copper surfaces exposed in urban and rural/coastal areas. The existence of sulfate salt agrees well with the XPS spectra.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 23 publications
(41 reference statements)
7
49
1
5
Order By: Relevance
“…The Cu 2p XPS spectra of copper exposed to an urban atmosphere in previous studies 21), 25) are completely different from those obtained in this study. For comparative purposes, the Cu 2p spectrum of copper exposed to an urban atmosphere is shown in Fig.…”
Section: ) 18)contrasting
confidence: 99%
See 3 more Smart Citations
“…The Cu 2p XPS spectra of copper exposed to an urban atmosphere in previous studies 21), 25) are completely different from those obtained in this study. For comparative purposes, the Cu 2p spectrum of copper exposed to an urban atmosphere is shown in Fig.…”
Section: ) 18)contrasting
confidence: 99%
“…While similar satellite peaks were previously observed for an as-cleaned copper surface, 21) in this study the copper surface was sputtered by Ar until carbon and oxygen were not observed in the spectra. Therefore, the initial surface conditions were different.…”
Section: ) 18)supporting
confidence: 82%
See 2 more Smart Citations
“…Copper is widely used in a number of critical electrical applications, and the problem and study of copper corrosion is a major area of research [1][2][3][4][5][6][7][8]. Previous researchers have studied the sulfidation of copper using SO 2 and H 2 S gas and found that these reactants interact at the wateroxide interface, possibly at copper oxide grain boundaries [5,[9][10].…”
Section: Background On Copper Sulfidationmentioning
confidence: 99%